Demonstrated Actions of Instructional Leaders - Petersen, George J. (Education Policy Analysis Archives, 1999)
To confirm perceptions, actions, and behaviors articulated by the district superintendents, triangulation interviews were conducted with school principals and school board members in each of the participating districts. A 52- item questionnaire was also administered to every principal and school board member in these districts. Responses of these personnel confirmed the articulated actions and behaviors of these superintendents in their promotion of the technical core of curriculum and instruction.